Psychosocial interventions for people with amyotrophic lateral sclerosis and motor neuron disease and their caregivers: a scoping review - Juyeon Oh; Jiwon An; Kyongok Park; Youngok Park (BMC, 2024)
Abstract Background As amyotrophic lateral sclerosis/motor neuron disease (ALS/MND) is a fatal progressive neurodegenerative disorder, patients experience severe impairments, with patients and family caregivers facing emotional distress and exhaustion. Several psychosocial interventions are aimed at providing tailored support for ALS/MND patients and caregivers. The aim of this study was to conduct a scoping review and present a comprehensive overview of psychosocial interventions designed for individuals and families affected by ALS/MND, while also pinpointing research gaps. Methods This scoping review utilized Arksey and O'Malley's methodological framework to investigate psychosocial interventions designed for individuals with ALS/MND and their families. The study adhered to the PRISMA-ScR checklist for reporting. Results A total of 27 articles describing 25 interventions met the inclusion criteria. The predominant interventions observed in the research encompassed education-related strategies, closely followed by behavior therapy, counseling, social support interventions, and psychotherapy interventions. Across the majority of the studies, findings indicated promising feasibility and acceptability of these interventions. Notably, a significant proportion of quantitative investigations yielded one or more statistically significant effects, while qualitative studies consistently reported favorable outcomes, including enhancements in well-being and heightened awareness of individual circumstances. Conclusions Given the progressive and debilitating nature of this condition, coupled with the absence of a cure, the adoption of a psychosocial approach can prove beneficial for both ALS/MND patients and their families. However, high-quality RCTs with a large sample size are recommended to examine and confirm the effectiveness.